(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Congestive cardiac failure may involve the renal function. Objective: The purpose of the present study was to describe the status of electrolyte and renal abnormalities in patients with congestive cardiac failure. Methodology: This was a cross-sectional study at Department of Medicine and Department of Cardiology at Dhaka Medical College Hospital, Dhaka, Bangladesh for six months after approval of the protocol on patients suffering from CCF. Study population were selected in the study group based on age more than 18 years with both sexes as well as diagnosed case of CCF and willing to participate. Result: A total number of 100 participants were included in this study. In addition Lab investigation showed mean serum creatinine 133.5±76.9 μmol/L. The mean serum sodium was 136.2±5.7 mmol/L. Hyponatraemia was present in 38.0% cases of the patients while 6.0% cases had hypenatraemia. The mean serum potassium was 4.3±0.7 mmol/L and hypokalaemia and hyperkalaemia were present in 14.0% and 6.0% of the patients respectively. The frequency of acute kidney injury (AKI) was 29.0% cases; however, 30.0% cases of total study population had chronic kidney disease (CKD). Conclusion: In conclusion majority patients have electrolyte disturbance among CCF patients. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):42-45